The Theater of José Saramago - Muñoz, Asunción (Escritura e Imagen, 2024)
This article analyzes the ideas contained in the theater of José Saramago. This analysis allows for a comparison of the fundamental concepts and the situations subjected to criticism by the author. It also highlights the relevance of this critical perspective, which is more extensively developed in some of his novels.